Motion coordination and path planning of robot system using MATLAB - Li, Weinan (Nanyang Technological University, 2022)
MRSs, or multi-robot systems, are extremely essential and meaningful in robotics research. A single-robot system or coordination, on the other hand, contains only one individual robot that can model itself, including the surroundings and even the interaction. In a single coordination system, the robot is often utilized to handle a job on its own. There are two keys that are far apart in space and must be activated simultaneously. As a result, one of the intrinsic limitations of a single-robot system is its restricted space. The project, in this report that I researched and analyzed the Intelligent motion coordination for a or multi ground robots. As well as the control of robots and path planning. In simulation part, I implemented robot’s motion and robot’s control by writing certain codes and algorithms. These simulations were implemented by me in MATLAB, ROS toolbox (Robot Operating System), Robotic playground, including stateflow, MATLAB function, PID control, and even image processing. Also in this project, the type of robot’s coordination was discussed, pros and cons.